2019
DOI: 10.1177/1049909119867046
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hospitalized Patients Screening Positive for Delirium

Abstract: Background: Delirium in the hospitals leads to worse outcomes for patients. There were no previous studies that characterize patients with delirium from multiple hospital locations. Objective: To describe patient characteristics screening positive for delirium and identify any correlations with hospital location and medication use. Design, Settings, Patients: Retrospective chart review of 227 hospitalized patients from a large, academic, tertiary referral, 2-campus health system. Patients were ≥18 years old an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Study inclusion criteria were: (1) hospitalised patients aged ≥18 years diagnosed with delirium according to the Diagnostic and Statistical Manual of Mental Disorders (DSM) or International Statistical Classification of Diseases and Health Related Problems (ICD) criteria, or validated tool, including the Confusion Assessment Method (CAM) 7 or CAM for the Intensive Care Unit (CAM-ICU), 17 Delirium Rating Scale Revised-98 (DRS-R98), 18 Nursing Delirium Screening Scale (Nu-DESC), 19 Memorial Delirium Assessment Scale (MDAS), 20 4AT 6 and Delirium Index (DI) 21 ; (2) baseline data from point of diagnosis of delirium or initial delirium assessment; (3) data from at least one repeated assessment within seven days from baseline (a clinically applicable timeframe; the average delirium episode has been suggested to be ~seven days 22 ); studies with further assessments beyond seven days were excluded; (4) data collected using neuropsychological assessment tools on at least one symptom domain of delirium (including general cognition, language, attention, level of arousal, memory, orientation, affect and distress), or tools measuring functional ability (e.g., mobility) in the context of repeated assessments. Studies reporting the overall score of a delirium-specific assessment tool (such as the DRS-R98) without reporting change in the individual neuropsychological or functional domains measured by the tool were excluded.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Study inclusion criteria were: (1) hospitalised patients aged ≥18 years diagnosed with delirium according to the Diagnostic and Statistical Manual of Mental Disorders (DSM) or International Statistical Classification of Diseases and Health Related Problems (ICD) criteria, or validated tool, including the Confusion Assessment Method (CAM) 7 or CAM for the Intensive Care Unit (CAM-ICU), 17 Delirium Rating Scale Revised-98 (DRS-R98), 18 Nursing Delirium Screening Scale (Nu-DESC), 19 Memorial Delirium Assessment Scale (MDAS), 20 4AT 6 and Delirium Index (DI) 21 ; (2) baseline data from point of diagnosis of delirium or initial delirium assessment; (3) data from at least one repeated assessment within seven days from baseline (a clinically applicable timeframe; the average delirium episode has been suggested to be ~seven days 22 ); studies with further assessments beyond seven days were excluded; (4) data collected using neuropsychological assessment tools on at least one symptom domain of delirium (including general cognition, language, attention, level of arousal, memory, orientation, affect and distress), or tools measuring functional ability (e.g., mobility) in the context of repeated assessments. Studies reporting the overall score of a delirium-specific assessment tool (such as the DRS-R98) without reporting change in the individual neuropsychological or functional domains measured by the tool were excluded.…”
Section: Selection Criteriamentioning
confidence: 99%
“…Given their critical status, which may include immobility, metabolic disorder, or being under the influence of medications, critically ill patients in the ICU, especially patients with mechanical ventilation, are at a high risk of developing delirium. The incidence of delirium in patients with mechanical ventilation has been reported to be 60% or higher (Li et al, 2018; Nguyen et al, 2020). Studies have shown that ICU delirium is an independent predictor in ICU patients of poor clinical prognoses such as prolonged mechanical ventilation, prolonged length of stay (LOS) in the ICU and the hospital, higher healthcare costs, and increased mortality (Marra et al, 2017; Senel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%